Mitochondrial superoxide increases excitatory synaptic strength in spinal dorsal horn neurons of neuropathic mice. Issue 1 (August 2018) - Bae, Chilman; Wang, Jigong; Shim, Hyun Soo; Tang, Shao-Jun; Chung, Jin Mo; La, Jun-Ho
Reactive oxygen species has been suggested as a key player in neuropathic pain, causing central sensitization by changing synaptic strengths in spinal dorsal horn neurons. However, it remains unclear as to what type of reactive oxygen species changes what aspect of synaptic strengths for central sensitization in neuropathic pain conditions. In this study, we investigated whether mitochondrial superoxide affects both excitatory and inhibitory synaptic strengths in spinal dorsal horn neurons after peripheral nerve injury. Upregulation of mitochondrial superoxide level by knockout of superoxide dismutase-2 exacerbated neuropathic mechanical hypersensitivity caused by L5 spinal nerve ligation, whereas downregulation of mitochondrial superoxide level by overexpression of superoxide dismutase-2 alleviated the hypersensitivity. In spinal nerve ligation condition, the frequency of miniature excitatory postsynaptic currents increased, while that of miniature inhibitory postsynaptic currents decreased in spinal dorsal horn neurons. Superoxide dismutase-2-knockout augmented, whereas superoxide dismutase-2-overexpression prevented, the spinal nerve ligation-increased miniature excitatory postsynaptic currents frequency. However, superoxide dismutase-2-knockout had no effect on the spinal nerve ligation-decreased miniature inhibitory postsynaptic current frequency, and superoxide dismutase-2-overexpression unexpectedly decreased miniature inhibitory postsynaptic current frequency in the normal condition. When applied to the spinal cord slice during in vitro recordings, mitoTEMPO, a specific scavenger of mitochondrial superoxide, reduced the spinal nerve ligation-increased miniature excitatory postsynaptic currents frequency but failed to normalize the spinal nerve ligation-decreased miniature inhibitory postsynaptic current frequency. These results suggest that in spinal dorsal horn neurons, high levels of mitochondrial superoxide increase excitatory synaptic strength after peripheral nerve injury and contribute to neuropathic mechanical hypersensitivity. However, mitochondrial superoxide does not seem to be involved in the decreased inhibitory synaptic strength in this neuropathic pain condition.